Optimalisasi peran pendidik dalam pendidikanmelalui integrasi potensi Qalb dan Aql - Basith, Yudril; Kurniawati Rahmah; Muhammad Zhulfan Ramadhan; Muchammad Tholchah (Indonesian Journal of Islamic Religious Education, 2024)
This article aims to find out the role of educators in optimising the potential of qalb and aql in the learning process and the strategies used by educators in integrating qalb and aql in the context of Islamic education. This article uses a qualitative literature method with a Semantic Literature Review (SLR) approach. Data collection is carried out by searching for data using the main keywords ‘qalb, aql and education’ through the Publish and Perish 8 application with a maximum search of 200 related journals with a citation count of 1346, h-index 19, and g-index 32. The author then focuses the study on papers published in 2023-2024 as many as 100 papers. Data analysis techniques in this study are planning, conducting and reporting. The findings reveal that educators play a multi-dimensional role in optimizing the potential of qalb and aql, acting as spiritual mentors, facilitators of intellectual growth, and exemplary role models. Strategies for qalb development include self-introspection, dhikr (remembrance of God), and fostering spiritual awareness. Meanwhile, strategies for aql development involve training students in logical and critical thinking, as well as integrating modern sciences with Islamic values. In today’s era of rapid technological advancement and shifting societal norms, this study highlights the critical importance of integrating spirituality and intellect in education to produce well-rounded individuals prepared to navigate the complexities of contemporary life while upholding ethical and spiritual values.